Surface modification and fibrovascular ingrowth of porous polyethylene anophthalmic implants - Yang, Hee Seok; Park, Kwideok; Son, Jun Sik; Kim, Jae-Jin; Han, Dong Keun; Park, Byung Woo; Baek, Se Hyun (POLYMER SOC KOREA, 2007)
The purpose of this study was to determine the effect of surface modification on the fibrovascular ingrowth into porous polyethylene (PE) spheres (Medpor (R)), which are used as an anophthalmic socket implant material. To make the inert, hydrophobic PE surface hydrophilic, nonporous PE film and porous PE spheres were subjected to plasma treatment and insitu acrylic acid (AA) grafting followed by the immobilization of arginine-glycine-aspartic acid (RGD) peptide. The surface-modified PE was evaluated by performing surface analyses and tested for fibroblast adhesion and proliferation in vitro. In addition, the porous PE implants were inserted for up to 3 weeks in the abdominal area of rabbits and, after their retrieval, the level of fibrovascular ingrowth within the implants was assessed in vivo. As compared to the unmodified PE control, a significant increase in the hydrophilicity of both the AA-grafted (PE-g-PAA) and RGD-immobilized PE (PE-g-RGD) was observed by the measurement of the water contact angle. The cell adhesion at 72 h was most notable in the PE-g-RGD, followed by the PE-g-PAA and PE control. There was no significant difference between the two modified surfaces. When the cross-sectional area of tissue ingrowth in vivo was evaluated, the area of fibrovascularization was the largest with PE-g-RGD. The results of immunostaining of CD31, which is indicative of the degree of vascularization, showed that the RGD-immobilized surface could elicit more widespread fibrovascularization within the porous PE implants. This work demonstrates that the present surface modifications, viz. hydrophilic AA grafting and RGD peptide immobilization, can be very effective in inducing fibrovascular ingrowth into porous PE implants.
Keywords: ADHESION PEPTIDES; ORBITAL IMPLANT; CELL-ADHESION; MEDPOR; HYDROXYAPATITE; STRESS